Determination of rational values of the parameters of the container depot - Aripov N.M.; Ilesaliev D.I.; Azimov F.K.; Ibragimova G.R. (Научно-технический вестник Брянского государственного университета)
Today, due to the increase in rail freight traffic, there is a shortage of containers, and the issue of shortage of containers has not been resolved for a long time. This substantiates the practical relevance of the study of container depots in railway transport. Another task is the development of mathematical models of the interconnection of the parameters of the container depot. Currently, there are several different methods and methods for calculating and determining the parameters of container sites, the analysis of which is given in the article. However, there is a need to supplement, clarify and unify the existing methods for calculating all kinds of parameters for a container depot, which justifies the theoretical relevance of the study. Connections with which the purpose of the article is to develop a methodology for the reliable determination of the most rational values of the parameters of the container terminal, thereby improving and increasing the level of customer service in transport in general. Research methods are based on a systematic analysis and generalization of existing methods and methods for calculating the capacity of container depots. The results of the study are presented by the developed methodology for determining the capacity of warehouses on railway transport, which provides a more qualified calculation and selection of container depot parameters, as well as a decrease in erroneous design decisions and an increase in the reliability of projects for the development and improvement of railway transport and the transport network as a whole.